2017
DOI: 10.1016/j.ijheatmasstransfer.2017.05.098
|View full text |Cite
|
Sign up to set email alerts
|

Topology optimization for heat transfer enhancement in Latent Heat Thermal Energy Storage

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(37 citation statements)
references
References 63 publications
(66 reference statements)
0
37
0
Order By: Relevance
“…The recent advances of Additive Manufacturing (AM) technologies are giving new momentum to this design methodology which is rapidly expanding in the energy field, for the design of e.g. thermoelectric components [31], Li-Ion batteries [32] and LHTES units [15,23].…”
Section: Topology Optimization Of Shell-and-tubes Lhtes Unitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent advances of Additive Manufacturing (AM) technologies are giving new momentum to this design methodology which is rapidly expanding in the energy field, for the design of e.g. thermoelectric components [31], Li-Ion batteries [32] and LHTES units [15,23].…”
Section: Topology Optimization Of Shell-and-tubes Lhtes Unitsmentioning
confidence: 99%
“…However, the design approaches commonly adopted lack generality as well as design freedom. Recently [15,23], we demonstrated the use of topology optimization as a systematic approach to find configurations of finned LHTES systems capable to deliver optimized time evolution of charging/discharging processes. Although these studies demonstrated high potential for design-driven innovations in the LHTES technology, they considered single-tube configurations, which are popular only for lab-scale or small facilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal integration of a thermoelectric cooler in a robotic downhole intervention tool using topology optimization to distribute conducting and insulating material in a 3D domain as well as fabrication and experimental validation of the prototype is presented in [19]. Pizzolato et al [20] apply density-based topology optimization to the design of conducting fins in a phase change material (PCM) storage tank modeling the solidification of the PCM as transient thermal diffusion problem both in 2D and 3D.…”
Section: Nomenclaturementioning
confidence: 99%
“…Sciacovelli et al [132] optimized tree-shaped fins for a double pipe heat exchanger by using numerical simulations to create a response surface in a 4-dimensional parameter space. Pizzolato et al [133] identified an optimal fin design for an annular heat exchanger with a topological optimization approach. More recently, Alayil et al [134] used an artificial neural network to find an optimal melting solution for a finned rectangular LHTSD with four independent parameters.…”
Section: Introductionmentioning
confidence: 99%